Choking, gagging and complementary feeding methods in the first year of life: a randomized clinical trial - Christielly Santos Silveira de Paiva; Leandro Meirelles Nunes; Juliana Rombaldi Bernardi; Paula Ruffoni Moreira; Adriela Azevedo Souza Mariath; Erissandra Gomes (Elsevier, 2023)
Objective: Compare the occurrence of choking and gagging in infants subjected to three complementary feeding (CF) methods. Methods: Randomized clinical trial with mother-infant pairs, allocated according to the following methods of CF: a) Parent-Led Weaning (PLW) - group control, b) Baby-Led Introduction to SolidS (BLISS), and c) mixed (initially BLISS and if the infant presents a lack of interest or dissatisfaction, PLW), with the last two methods guided by the infant. Mothers received nutritional intervention on CF and prevention of choking and gagging according to the method at 5.5 months of age and remained in follow-up until 12 months. Frequencies of choking and gagging were collected by questionnaire at nine and 12 months. The comparison between groups was performed using the analysis of variance test (p < 0.05). Results: 130 infants were followed, and 34 (26.2%) children presented choking between six and 12 months of age, 13 (30.2%) in PLW, 10 (22.2%) BLISS, and 11 (26.2%) mixed method, no significative difference between methods (p > 0.05). The choking was caused mainly by the semi-solid/solid consistency. Moreover, 100 (80%) infants aged from six to 12 months presented gagging and their characteristics were not statistically different among groups (p > 0.05). Conclusion: Infants following a baby-led feeding method that includes advice on minimizing choking risk do not seem more likely to choke than infants following traditional feeding practice that includes advice on minimizing choking risk.